A Cross-Sectional Study on Side Effects of “Corbevax” Covid-19 Vaccine among 12- to 14-Year Age Group in a Tertiary Care Hospital in Meerut, Uttar Pradesh - Chhaya Mittal; Harimu Bargayary; Mohit Saini (Indian Journal of Community Medicine)
Background: The first mass vaccination program for COVID-19 in India started on January 16, 2021. Initially, Covaxin and Covishield were used. Later, the Government of India has approved the usage of Corbevax, a Hyderabad-based biological E SARS-CoV-2 (COVID-19) vaccine among 12- to 14-year age group from March 16, 2022. Corbevax vaccination was started in our hospital setting on March 19, 2022, for 12- to 14-year age group. Monitoring safety of any vaccine is of importance in a real-world setting. Limited study has been performed till date on side effects of Corbevax vaccine. Therefore, this study has been planned to assess the side effects after Corbevax vaccination among 12- to 14-year age group in a tertiary care hospital setting in Meerut district. To assess the side effects after Corbevax vaccination among 12- to 14-year age group in a tertiary care hospital setting in Meerut district. Tertiary care hospital setting and cross-sectional study design. Methods and Material: A cross-sectional study was conducted among 270 study participants. Sample size was calculated assuming 50% prevalence of side effects after vaccination. Study subjects were selected by using simple random sampling among the beneficiaries of a tertiary care center. Data were collected using a pretested semistructured questionnaire. Proportions, Chi-square test. Results: Of all the participants, 41.48% had developed side-effects with pain at site of injection being the most commonly reported symptom (64.29%), and about half among those affected had resolved spontaneously. Conclusions: The vaccine causes only mild symptoms and is safe for use in children.